(untitled) (Journal of actual problems of jurisprudence, 2019)
This article discusses the formation of the legal migration policy of the Republic of Kazakhstan. On the theoretical and legal positions of the comparative analysis of the existing definitions of legal migration policy, suggested author’s definition. It is proved that regular updating of the migration legislation meet the realities of the modern state-legal development of the Republic of Kazakhstan. It was determined that the main directions of migration and legal policy of the Republic of Kazakhstan are implemented in the following areas: the formation of the population, repatriation, industrial-innovative development of Kazakhstan and the regulation of internal migration flows. Keywords: migration, the formation of the population, repatriation, internal migrants, migration and legal policy, immigration legislation.